New Biomarkers for Atherothrombosis in Antiphospholipid Syndrome: Genomics and Epigenetics Approaches - Lopez-Pedrera, Chary; Barbarroja, Nuria; Patiño-Trives, Alejandra Mª; Collantes, Eduardo; Aguirre, Mª Angeles; Perez-Sanchez, Carlos (Frontiers in Immunology, 2019)
Antiphospholipid Syndrome (APS) is an autoimmune disorder, characterized by pregnancy morbidity and/or a hypercoagulable state involving the venous or the arterial vasculature and associated with antiphospholipid antibodies (aPL), including anti-cardiolipin antibodies (aCL), anti-beta2-glycoprotein I (anti-ß2GPI) and Lupus anticoagulant (LA). In recent years there have been many advances in the understanding of the molecular basis of vascular involvement in APS. APS is of multifactorial origin and develops in genetically predisposed individuals. The susceptibility is determined by major histocompatibility complex (MHC). Different HLA-DR and HLA-DQ alleles have been reported in association with APS. Moreover, MHC II alleles may determine the autoantibody profile and, as such, the clinical phenotype of this disease. Besides, polymorphisms in genes related to the vascular system are considered relevant factors predisposing to clinical manifestations. Antiphospholipid antibodies (aPL) induce genomic and epigenetic alterations that support a pro-thrombotic state. Thus, a specific gene profile has been identified in monocytes from APS patients -related to aPL titers in vivo, and promoted in vitro by aPL- explaining their cardiovascular involvement. Regarding epigenetic approaches, we previously recognized two miRNAs (miR-19b/miR-20a) as potential modulators of tissue factor, the main receptor involved in thrombosis development in APS. aPLs can further promote changes in the expression of miRNA biogenesis proteins in leukocytes of APS patients, which are translated into an altered miRNA profile and, consequently, in the altered expression of their protein targets related to thrombosis and atherosclerosis. MicroRNAs are further released into the circulation, acting as intercellular communicators. Accordingly, a specific signature of circulating miRNAs has been recently identified in APS patients as potential biomarkers of clinical features. Genomics and epigenetic biomarkers might also serve as indices for disease progression, clinical pharmacology, or safety, so that they might be used to individually predict disease outcome and guide therapeutic decisions. In that way, in the setting of a clinical trial, novel and specific microRNA–mRNA regulatory networks in APS, modified by effect of Ubiquinol treatment, have been identified. In this review, current and previous studies analyzing genomic/epigenomic changes related to the clinical profile of APS patients, and their modulation by effect of specific therapies, are discussed.